Innovative electrochemical biosensor with nitrifying biofilm and nitrite oxidation signal for comprehensive toxicity detection in Tuojiang River. (15th April 2023) - Wang, Jingting; Dong, Chong; Li, Qiquan; Yang, Xu; Li, Daping; Zhang, Lixia; Zhang, Yifeng; Zhan, Guoqiang
Highlights: A novel and rapid detection method was developed for water comprehensive toxicity. Accuracy of the biosensor was confirmed by CCK-8 kit and CLSM method. Biosensor was successfully used to detect comprehensive toxicity in the Tuojiang River. This method provides a useful supplement to traditional water quality detection. Abstract: Water toxicity detection, as a valuable supplement to conventional water quality measurement, is an important method for evaluating water environmental quality standards. However, the toxicity of composite pollutants is more complicated due to their mixture effects. This study developed a novel, rapid and interference-resistant detection method for water toxicity based on an electrochemical biosensor using peak current from nitrite oxidation as a signal. Toxicants could weaken the characteristic peak current of nitrite to indicate the magnitude of toxicity. The proof-of-concept study was first conducted using a synthetic water sample containing trichloroacetic acid (TCAA), and then the results were compared with those of the traditional toxicity colorimetric method (CCK-8 kit) and laser confocal microscopy (CLSM). The accuracy of the biosensor was further verified with water samples containing individual pollutants such as Cd 2+ (50–150 μg/L), Cr 6+ (20–80 μg/L) mixture, triclosan (TCS; 0.1–1.0 μg/L) and TCAA (10–80 μg/L), or a mixture of the above. The viability of the sensor was further validated with the actual water sample from the Tuojiang River. The results demonstrated that although the concentration of a single conventional pollutant in water did not exceed the discharge standard for surface water, the comprehensive toxicity of natural water should not be ignored. This method could be a beneficial supplement to conventional water quality detection to understand the characteristics of the water, and thus contribute to the next stage of water treatment. Graphical abstract: Image, graphical abstract